Diminutives in anthroponyms of kazakh and turkish languages - Бaлaбековa Н. Р. (Journal of Oriental Studies, 2018)
This article describes the insufficiently explored subject in linguistics Turkic languages – diminutive and their application in anthroponyms Kazakh and Turkish languages. Provide explanations on the terms diminutive and anthroponyms. On examples in the Kazakh and Turkish individually analyzed diminutive affixes. The test question is one of the insufficiently known until now the actual fact as a separate category in the diminutive general linguistics, including in Turkic studies.